Application of the C45 Decision Tree Method in Evaluating the Potential and Contribution of Retribution to Pad: Case Study of Barru Regency - Arfiansyah, Wahyu; Zainal, Muhammad; Wahyuddin, Wahyuddin; Masnur, Masnur (Journal of System and Computer Engineering, 2025)
Local Original Revenue (PAD) is a vital source for financing regional development, with levies as the main component. However, the main challenge faced is the inability of conventional evaluation methods to identify factors that influence the contribution of levies to PAD effectively. This study aims to evaluate the potential and contribution of levies to PAD by applying the Decision Tree C4.5 method. This research method uses a quantitative data-based approach, by analyzing tax data from various sectors, including Hotel Tax, Parking Tax, Entertainment Tax, and Advertising Tax. The results of the study indicate that the C4.5 method successfully identified more complex contribution patterns and provided a deeper understanding of the influence of seasonal and external factors on tax contributions. Entertainment Tax and Hotel Tax showed the largest contributions in certain periods, while Parking Tax showed greater stability throughout the year. The implications of this study indicate that the application of C4.5 can improve the effectiveness of PAD management, by providing a basis for tax policies that are more data-based and responsive to economic and seasonal fluctuations.